Kompleksitas Perusahaan, Client Importance dan Volatilitas Idiosinkratik - Rinta, Mei (E-Jurnal Akuntansi, 2021)
This study examines the influence between company complexity and client importance on idiosyncratic volatility. The research sample are listed companies in all industries except financial services and banking for period 2014-2018. The dependent variable is idiosyncratic volatility, while the independent variable is company complexity and client importance. Multiple linear regression was used to test. The results showed that there was a significant positive effect of client importance on the dependent variable and a significant negative effect on company complexity on the dependent variable. This means that business line information and auditor-related factors are a signal for investors to react to company shares. Keywords: Complexity Of The Company; Client Importance; Idiosyncratic Volatility.